ANALISIS FAKTOR KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA NIAT BELI ULANG - Yoanita Rahesa Wijaya; Endang Tjahjaningsih (STEKOM PRESS, 2022)
One way to maintain business continuity in the midst of intense competition is to maintain customer satisfaction. Product diversity is considered important here because the more diverse the number and types of products sold in one place, the customer will feel satisfied if he makes a purchase at that place and he does not need to make a purchase elsewhere. In addition, good service makes it easier for customers to find the goods they want. The purpose of this study was to analyze and explain the effect of product diversity, service quality mediated by the effect of customer satisfaction on repurchase intentions. The analysis technique that will be carried out in this research is descriptive analysis, instrument test, multiple linear regression analysis, model test, and hypothesis testing. The minimum sample selected in the study was 92 respondents. The adjusted R² value of 0.301 means that the effect of the product diversity variable (X1) and service quality variable (X2) on customer satisfaction (Y1) is 30.1%. The adjusted R² value of 0.422 means that the magnitude of the influence of the product diversity variable (X1), service quality variable (X2) and customer satisfaction (Y1) on repurchase intention (Y2) is 42.2%